Writing in a Polyaniline Film with Laser Beam and Stability of the Record: A Raman Spectroscopy Study - Zuzana Morávková; Patrycja Bober (International Journal of Polymer Science)
Lines were drawn on polyaniline (PANI) salt films with laser beam, and then the samples were left to age in air at room temperature. Both the irradiated and intact parts of the sample and their ageing were studied with Raman spectroscopy. It was found that the laser-written record is reasonably stable. The degradation of polyaniline by laser irradiation and ageing was compared to the changes in PANI during heating. In all cases, deprotonation and crosslinking of PANI chains proceed but the relative rates of the processes vary with degradation conditions.